2021
DOI: 10.1111/adj.12836
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of the public dental workforce on the dental management of people with special needs

Abstract: Background People with special health care needs continue to have difficulties accessing regular dental care partly due to oral health professionals feeling they lack the knowledge and experience to provide treatment to these individuals. Methods Qualitative interviews and focus groups provided an insight into the types and nature of supports that oral health professionals working in the Australian public dental system desired and felt may improve their willingness and/or ability to treat patients with special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 44 publications
(77 reference statements)
1
14
0
Order By: Relevance
“…The physicians who were interviewed expressed the idea that a top-down approach could facilitate increased access to health care by people with special needs and highlighted the need for a multidisciplinary team approach. This suggestion was similar to other research that called for interprofessional collaboration in the healthcare of PWDs [ 8 , 24 ]. Research has also advocated for improved use of publicly-funded dental services that have been integrated with other services that benefit this population [ 16 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The physicians who were interviewed expressed the idea that a top-down approach could facilitate increased access to health care by people with special needs and highlighted the need for a multidisciplinary team approach. This suggestion was similar to other research that called for interprofessional collaboration in the healthcare of PWDs [ 8 , 24 ]. Research has also advocated for improved use of publicly-funded dental services that have been integrated with other services that benefit this population [ 16 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Recent research on the barriers that caregivers of people with special needs encounter, include, but are not limited to, inaccessibility to buildings or facilities, discrimination by healthcare staff and lack of information, also strengthen the need for this type of research [ 6 , 7 ]. Furthermore, access to oral healthcare may be affected by both the service provided and the personnel [ 8 ]. This inevitably leads to reduced dental care in PWDs.…”
Section: Introductionmentioning
confidence: 99%
“…A barrier for many oral health professionals is their perceived lack of knowledge or training in managing those with special needs [ 2 , 4 6 ]. The ability to find suitably-trained and experienced dentists has been identified as a key barrier to accessing regular and ongoing oral health care by individuals with disabilities and their carers [ 2 ] and dental specialists in this field [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to find suitably-trained and experienced dentists has been identified as a key barrier to accessing regular and ongoing oral health care by individuals with disabilities and their carers [ 2 ] and dental specialists in this field [ 7 ]. Oral health professionals have discussed their limited exposure to treating individuals with special needs as part of their training and difficulty with accessing ongoing professional development in this area as concerns [ 5 , 6 ]. However, many have also suggested that receiving additional support may improve both their willingness to treat these individuals and reduce their reliance on referral to specialists where these patients often encounter long waiting lists [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation